2021
DOI: 10.1021/jacs.1c01180
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Spectroscopy Correlations for Intermediate Q of Soluble Methane Monooxygenase: Insights from QM/MM Calculations

Abstract: The determination of the diiron core intermediate structures involved in the catalytic cycle of soluble methane monooxygenase (sMMO), the enzyme that selectively catalyzes the conversion of methane to methanol, has been a subject of intense interest within the bioinorganic scientific community. Particularly, the specific geometry and electronic structure of the intermediate that precedes methane binding, known as intermediate Q (or MMOH Q ), has been debated for over 30 years. Some repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 133 publications
(358 reference statements)
3
43
0
1
Order By: Relevance
“…From the calculated Mössbauer spectrum of different conformers of Int II , the square-pyramidal isomer with the axial nitrogen SQP-N ax (δ = 0.47 mm/s, ΔE Q = 0.78 mm/s) gives a value relatively close to the experimental result (δ = 0.57 mm/s, ΔE Q = 0.40 mm/s) compared to the other models in terms of the isomer shift 140 , 143 146 ( Figure 7 b). A point to note is the quadrupole splitting is not considered for correlation as previous studies have shown that the predicted isomer shifts tend to be more reliable than the calculated quadrupole splittings.…”
Section: Computational Calculations: Correlation To Spectroscopysupporting
confidence: 68%
See 2 more Smart Citations
“…From the calculated Mössbauer spectrum of different conformers of Int II , the square-pyramidal isomer with the axial nitrogen SQP-N ax (δ = 0.47 mm/s, ΔE Q = 0.78 mm/s) gives a value relatively close to the experimental result (δ = 0.57 mm/s, ΔE Q = 0.40 mm/s) compared to the other models in terms of the isomer shift 140 , 143 146 ( Figure 7 b). A point to note is the quadrupole splitting is not considered for correlation as previous studies have shown that the predicted isomer shifts tend to be more reliable than the calculated quadrupole splittings.…”
Section: Computational Calculations: Correlation To Spectroscopysupporting
confidence: 68%
“…The calculation of observables such as the spectroscopic and kinetic properties can serve as important guides in validating the results of calculations and identifying the nature of the observed intermediates. 140 Thus, correlation of the experimental results to the theoretical calculations are pursued in the subsequent section for electronic and structural elucidation of the reaction components (see Table S33 , SI for a comparative overview). We first apply this approach to the precursor complex 1 (see SI , computational section for details), to establish a benchmark for the correlations before extending this analysis to the geometric and electronic structures of the reaction intermediates ( Int I and Int II ), which are discussed in the next part of the manuscript.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For OC −OH/O models possessing an OH–Fe 2 –(μ-O)–Fe 1 O structure, the Fe 1 O bond weakens the Fe 1 –(μ-O) bond, resulting in a shorter Fe 2 –(μ-O) bond, localizing ν as (Fe–O–Fe) on the Fe 2 side. This facilitates ν­(Fe–OH) + ν as (Fe–O–Fe) coupling, resulting in a symmetric mode ν 2 which would agree with the 690 cm –1 experimental data (Figure , bottom row, red box), as anticipated in a recent computational study of Q . Isotope labeling with 18 O 2 must be incorporated into the μ-O bridge to correlate to the decay product T, as well as either into the OH - or O terminal ligands.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers still pay considerable attention to binuclear oxo-bridged non-haem iron complexes (containing the Fe–O–Fe unit) due to their potential uses in biological processes, catalysts, magnetic materials, etc. 1–8 We can design an appropriate ligand to chelate metal centers in a special frame and control the electron withdrawal from the metal ion core, thereby modifying the intramolecular exchange interaction. 9,10 Binuclear oxo-bridged complexes mainly contain tribridged-, 11 dibridged- 12,13 and monobridged- 14 species.…”
Section: Introductionmentioning
confidence: 99%